(untitled) (Revista Sistemas de Producción Agroecológicos, 2016)
The ethological behavior of six sows was evaluated (Crossbred Landrace x Pietrain) under the system of open field production using a density of 450 m2/sow in the two seasons of the year (dry and rainy), in order to determine its behavioral characteristics. Adaptability observed in principle, recognition, individual and group behavior, response to stimuli of danger or threat, food selection, hours and rest areas, rooting, or excretion and dry areas. Maternal behavior was also observed, in order to determine ethological features in the open field system. A daily record of environmental parameters was carried as maximum and minimum temperatures (from 7:00 am to 5:00 pm), as well as precipitation, to determine the impact of these conditions in the sows. Feeding the animals it was based on a balanced diet made on the same site, 2 kg/sow/day and 200 g additional per piglet in lactating animals. The food was supplied narrowly in two servings a day (7:30 a.m. and 4:30 p.m.). The reproductive management was based on the use of a commercial player (Landrace x Pietran), performing the service once identified the zeal. To establish the diversity, coverage and degree of dominance of plant species appraisals were conducted. Shares of water consumption, grazing, exploration, rest, swim in the pool and fighting were highly influenced by the time of year (P<0.001), changes batch activities regarding changes recorded ambient temperature were also evident. The behavior of the sows suggests an interesting ability to adapt to the conditions of temperature, precipitation and soil characteristics (drainage), as well as the management system. Although there are coincidences with literature reports, required further animal behavior in the conditions of the Orinoquía and its dynamics of precipitation, solar radiation and ambient temperature for the design of appropriate facilities to ensure comfort conditions and management strategies.